CXCR6 regulates localization of tissue-resident memory CD8 T cells to the airways - Wein, Alexander N; McMaster, Sean R; Takamura, Shiki; Dunbar, Paul R; Cartwright, Emily K; Hayward, Sarah L; McManus, Daniel T; Shimaoka, Takeshi; Ueha, Satoshi; Tsukui, Tatsuya; Masumoto, Tomoko; Kurachi, Makoto; et al. (The Journal of experimental medicine, 2019)
Resident memory T cells (T cells) are an important first-line defense against respiratory pathogens, but the unique contributions of lung T cell populations to protective immunity and the factors that govern their localization to different compartments of the lung are not well understood. Here, we show that airway and interstitial T cells have distinct effector functions and that CXCR6 controls the partitioning of T cells within the lung by recruiting CD8 T cells to the airways. The absence of CXCR6 significantly decreases airway CD8 T cells due to altered trafficking of CXCR6 cells within the lung, and not decreased survival in the airways. CXCL16, the ligand for CXCR6, is localized primarily at the respiratory epithelium, and mice lacking CXCL16 also had decreased CD8 T cells in the airways. Finally, blocking CXCL16 inhibited the steady-state maintenance of airway T cells. Thus, the CXCR6/CXCL16 signaling axis controls the localization of T cells to different compartments of the lung and maintains airway T cells.